2022
DOI: 10.1371/journal.pone.0269691
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of subclinical ventricular systolic dysfunction assessed using global longitudinal strain in liver cirrhosis: A systematic review, meta-analysis, and meta-regression

Abstract: Global longitudinal strain (GLS) can identify subclinical myocardial dysfunction in patients with cirrhosis. This systematic review aims to provide evidence of a possible difference in GLS values between patients with cirrhosis and patients without cirrhosis. Studies from inception to August 11, 2021, were screened and included based on the inclusion criteria. The Newcastle Ottawa Scale was used to assess the quality of nonrandomized studies. Meta-analyses were conducted with subsequent sensitivity and subgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(221 reference statements)
0
0
0
Order By: Relevance
“…In 19 of these studies reporting GLS values, a total of 1017 patients and 609 controls were included. The investigators found lower absolute GLS values in patients with liver cirrhosis than in controls [Mean Difference −1.43% (−2.79%-0.07%), p = 0.04] [46]. However, this analysis reported increased heterogeneity between studies (I 2 = 0.95, p < 0.00001), did not include all relevant studies [36,47], including a study in non-cirrhotic patients and namely those with chronic hepatitis B [48], and incorporated a study that calculated longitudinal strain with cardiac magnetic resonance [49].…”
Section: How Different Are Left Ventricular Strain Values Of Cirrhoti...mentioning
confidence: 99%
“…In 19 of these studies reporting GLS values, a total of 1017 patients and 609 controls were included. The investigators found lower absolute GLS values in patients with liver cirrhosis than in controls [Mean Difference −1.43% (−2.79%-0.07%), p = 0.04] [46]. However, this analysis reported increased heterogeneity between studies (I 2 = 0.95, p < 0.00001), did not include all relevant studies [36,47], including a study in non-cirrhotic patients and namely those with chronic hepatitis B [48], and incorporated a study that calculated longitudinal strain with cardiac magnetic resonance [49].…”
Section: How Different Are Left Ventricular Strain Values Of Cirrhoti...mentioning
confidence: 99%